CONSTRUCTION OF LEGAL CULTURE MODEL FOR CORRUPTION PREVENTION THROUGH SOCIAL MEDIA IN INDONESIA - Riwanto, Agus (Jurnal Hukum dan Peradilan, 2022)
Fighting corruption is done not only repressively but also preventively through a legal culture approach. This article examines and explores the construction of a legal culture model to prevent corruption through social media. Because the rampant corruption in Indonesia is also caused by cultural factors, including the weak culture of religiosity, strong kinship culture, and paternalistic culture. The research method used is non-doctrinal or social-legal with a conceptual approach. This study found that preventing corruption from the aspect of legal culture can be done by utilizing internet-based culture in the new age in various social media, such as Facebook, Twitter, WhatsApp, Instagram, and blogs, as a tool for social movements to prevent corruption. Because philosophically, the media functions for surveillance, interpretation, linkage, and the transmission of values and entertainment simultaneously. The urgency of the role of the media as a tool for the anti-corruption community movement or civil society is because, in the tradition of internet-based democracy or e-democracy, social media is placed as the fourth pillar of democracy or the fourth estate democracy for a balancer in the supervision of democratic governance. Several construction models of the legal culture of the anti-corruption watchdog social movement are needed through social media, namely, the model for forming a non-profit social media organization. Second, the model creates an anti-corruption icon on social media. Third, a model for the legal protection of the anti-corruption movement on social media.